Adoption of Information Technology and its effect on Cooperative Performance in Egba Division, Ogun State, Nigeria - Oyebanjo, O.; Ologbon, O.A. C.; Oshodi, D. A.; Oluwasanya, O. P.; Dada, O. M. (NIU Journal of Social Sciences, 2020)
Cooperative is a common platform for addressing contemporary financial challenges in a fast growing economy. The manual accounting systems among cooperatives are very slow, leave high margin of errors and create opportunities for abuse with negative impact on cooperative performance. The study examined factors affecting information technology (IT) adoption and its effect on cooperative performance in Egba Division, Ogun State, Nigeria. Primary data were collected from 122 respondents by multi-stage sampling techniques through questionnaire. Data were analysed by descriptive statistics, Binary Logit and Cobb-Douglas function. The result shows that average respondent was 32.8 years old. Male (80.3%) dominated cooperative management, 64.8% were married, 31.2% had maximum of secondary education. Cooperative membership was 10 – 58 persons. The major IT facilities adopted were office phone (84.4%), computer system (63.9%) and television (45.9%). Some managers (23.3%) were computer illiterate. Regression estimates revealed that age (p < 0.01), education (p < 0.01), experience (p < 0.01) and computer literacy (p < 0.01) of cooperative managers affected IT adoption while cooperative performance was promoted by computer system (p<0.01), office phone (p<0.01), television (p<0.01) and managers’ experience (p<0.01). The major constraints against IT adoption were high cost of IT (63.1%) and low membership/ finance (45.9). Therefore, government should ensure policy that will increase membership participation and finance in cooperatives. It is recommended that minimum cooperative membership for registration should be twenty (20) persons. Computer training should be compulsory for managers/ staff under the principle of cooperative education. IT adoption should become a policy in the bye-law. Keywords : Cooperatives, adoption, information technology, performance, Logit model